Reduction of iodinated contrast load with the renal artery catheterization technique during endovascular aortic repair - Murat Canyiğit; Levent Çetin; Emrah Uğuz; Oktay Algın; Aslıhan Küçüker; Halil Arslan; Erol Şener (Diagnostic and Interventional Radiology, 2013)

(untitled)
PURPOSEWe aimed to present our clinical experience with the renal artery catheterization (RAC) technique, which reduces the volume of intra-arterial contrast media (ICM) used during endovascular aortic repair (EVAR), and describe the short-term results of this technique. MATERIALS AND METHODSWe retrospectively evaluated 16 patients (15 males and one female) who underwent EVAR between March 2011 and February 2012 using the RAC technique for an abdominal aortic aneurysm. A Simmons-1 catheter was preferred for renal artery cannulation. The mean age of the patients at the time of treatment was 70 years (range, 61–82 years). Fifteen cases were fusiform aneurysms, and one case was a saccular aneurysm. Creatinine and estimated glomerular filtration rate (eGFR) values were recorded before the procedure and during the first 72 hours postprocedure. RESULTSBifurcated stent grafts were implanted with 100% procedural success using the RAC technique. The inferiorly positioned renal artery was cannulated with a Simmons-1 catheter in the first five patients, and was maintained at the level of the renal artery orifice in the remaining patients. The mean volume of the ICM used was 47 mL (range, 23–83 mL). The creatinine and eGFR values were not significantly different between the pre- and postoperative periods (P > 0.05). CONCLUSIONReducing the volume of ICM used during EVAR is critical for protecting renal function. The RAC technique is a safe and effective method in appropriate patients when performed by experienced clinicians.